2020
DOI: 10.1177/1078155220957738
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist value-added to neuro-oncology subspecialty clinics: A pilot study uncovers opportunities for best practices and optimal time utilization

Abstract: Purpose To evaluate neuro-oncology clinician time utilization for medication management and identify a cost beneficial role for integration of a dedicated pharmacy specialists. Methods A pharmacist was temporarily integrated into a neuro-oncology clinic for a 30-day period to evaluate the clinical practice and perform a 14-day clinical chart evaluation and patient interactions as part of a single institutional exploratory analysis. The pharmacist completed screenings for drug-drug interactions, new therapies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This time equated to 0.4-0.5 pharmacist FTE (0.125 physician FTE) and additional physician patient-facing-encounters to improve access to care and increase revenue potential. 28 Another site recently described a service expansion project for anticoagulation management of oncology patients and demonstrated an estimated 325 h' time saved and a predicted $93,000 cost avoidance to the clinic staff when a pharmacist managed the anticoagulation. The organization also found that quality of care improved demonstrated by the International Normalized Ratio (INR) in goal range in 83% of patients monitored by pharmacists compared to 68% if not managed by a pharmacist 29 Lastly, ambulatory clinic areas present opportunities for direct revenue generation by billing for pharmacist services.…”
Section: Case Example 2 Ambulatory Clinic Practicementioning
confidence: 99%
“…This time equated to 0.4-0.5 pharmacist FTE (0.125 physician FTE) and additional physician patient-facing-encounters to improve access to care and increase revenue potential. 28 Another site recently described a service expansion project for anticoagulation management of oncology patients and demonstrated an estimated 325 h' time saved and a predicted $93,000 cost avoidance to the clinic staff when a pharmacist managed the anticoagulation. The organization also found that quality of care improved demonstrated by the International Normalized Ratio (INR) in goal range in 83% of patients monitored by pharmacists compared to 68% if not managed by a pharmacist 29 Lastly, ambulatory clinic areas present opportunities for direct revenue generation by billing for pharmacist services.…”
Section: Case Example 2 Ambulatory Clinic Practicementioning
confidence: 99%